2019
DOI: 10.1021/acsami.9b01826
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Loaded Cubosomes Functioning as an Antimicrobial Unit against Escherichia coli

Abstract: Dispersions of cubic liquid crystalline phases, also known as cubosomes, have shown great promise as delivery vehicles for a wide range of medicines. Due to their ordered structure, comprising alternating hydrophilic and hydrophobic domains, cubosomes possess unique delivery properties and compatibility with both water-soluble and -insoluble drugs. However, the drug delivery mechanism and cubosome interaction with human cells and bacteria are still poorly understood. Herein, we reveal how cubosomes loaded with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 57 publications
3
29
1
Order By: Relevance
“…The authors suggested that the bactericidal effect was due to physical interaction between the product and the bacterial membrane and not solely to the release of the peptide. Moreover, they noted that the presence of LL-37, the chosen AMP, constituted of a secondary structure of a linear α-helix increased the affinity of CB to bacterial membranes ( Boge et al, 2017 ; Boge et al, 2019a ; Boge et al, 2019b ).…”
Section: Drug Development and Formulation Approaches For Amp Applicationsmentioning
confidence: 99%
“…The authors suggested that the bactericidal effect was due to physical interaction between the product and the bacterial membrane and not solely to the release of the peptide. Moreover, they noted that the presence of LL-37, the chosen AMP, constituted of a secondary structure of a linear α-helix increased the affinity of CB to bacterial membranes ( Boge et al, 2017 ; Boge et al, 2019a ; Boge et al, 2019b ).…”
Section: Drug Development and Formulation Approaches For Amp Applicationsmentioning
confidence: 99%
“…[61][62][63] Cubosomes have been shown to provide a certain degree of in vivo protection to biomolecules that would otherwise be sensitive to enzymatic degradation, highly advantageous in the delivery of immunogenic therapeutics. [62][63][64] Timely and impressive work from Sarkar et al used cubosomal particles for the delivery of genetic material, attributing improved delivery efficiency to particle topology. 65 There is potential for enhancing site specificity by leveraging the polymeric corona, and some preliminary work has gone into producing stimuli-responsive cubosomal particles for environmentally triggered cargo release.…”
Section: Cubosomesmentioning
confidence: 99%
“…Although various mimetic bacterial membranes have been reconstituted on the surface for antibiotics-membranes studies, to reduce the total charge of lipid mixtures, most of the lipids compositions were mixed with zwitterionic phosphatidylcholines (PC), which were not found in bacterial membranes. Those membranes include zwitterionic single-lipid 1-palmitoyl-2oleoyl-sn-glycero-3-phosphocholine (POPC) 56 and (dioleylphosphatidylcholine) DOPC 57,58 bilayer, or anionic POPG:-POPC 59 and 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC): 1,2-dimyristoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DMPG) 60 with less than 25% of the negative charges to represent the bacterial membrane. In 2015 Lind and coworkers extracted lipids from E. coli with low net negative charges (75% PE, 13% PG, and 12% CL) 61 and had successfully reconstituted the bacterial membrane by the vesicle rupture for NR study.…”
Section: Neutron Reflectometry (Nr)mentioning
confidence: 99%